Efecto del H2S en la Susceptibilidad al Agrietamiento de Dos Aceros Microaleados para Tubería - Serna, Sergio; Villalobos, Julio C.; Flores, Osvaldo; Martínez, Horacio; López, Edgar; Campillo, Bernardo (KnE Engineering, 2018)
Cracking in sour media modes were observed, and these were related mainly to the microstructure produced during the thermomechanical process of two microalloyed steels grade API X 52. Through the use of linear elastic fracture mechanics modified specimens. Steels loaded at similar initial stress intensity factors showed different cracking modes that were related directly to their different microstructures. Steels microstructures indicate different fabrication routes. Testing temperature played an important role on switching the cracking characteristics being remarkable by the ferrite-pearlite steel microstructure. A banded microstructure is susceptible to the effects of hydrogen at room T. While, an acicular ferrite microstructure with carbides patches at grain boundaries is susceptible to anodic dissolution in front of the crack tip, no matter the temperature being tested. Key words: microalloyed steels, sour service, cracking modes, microstructure.